PEDAGOGICAL-PSYCHOLOGICAL WORK WITH PRIMARY GRADE STUDENTS - Maryambibi Djumaniyazovna Abdullayeva; Dildoraxon Nizomova (Web of Journals Publishing, 2025)
The pedagogical and psychological work carried out with primary school students is a critical component of fostering their academic, emotional, and social development. This paper aims to explore the foundational strategies, methodologies, and outcomes of such practices within the educational institutions of Uzbekistan. By addressing the unique needs and characteristics of primary school students, educators can promote a holistic learning environment that enhances both cognitive and emotional growth. The study examines various approaches, drawing upon contemporary theories and practices to provide practical insights for educators in teacher-training institutes.
Keywords: Pedagogical work, psychological approaches, primary school students, educational development, cognitive growth, emotional support, Uzbekistan.